GE_GERICHTE P/2671/2013 vom 14. Dezember 2016 - GE Cour de justice (2016)
USURE(DROIT PÉNAL) ; CONTRAINTE(DROIT PÉNAL) ; FIXATION DE LA PEINE ; INFRACTION PAR MÉTIER ; CONFISCATION(DROIT PÉNAL) ; CRÉANCE | .1 CP 157